The Flipped Classroom Model as a Pedagogical Innovation to Enhance Mufradat Mastery at the Elementary Level - Narul Hasyim Muzadi; Ahmad Mubaligh; Laily Fitriani (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Mufradat mastery is a very important basic component in Arabic learning. However, mufradat learning at the Madrasah Ibtidaiyah level still faces various obstacles, such as low student absorption and the use of conventional approaches that do not involve active student participation. This study aims to measure the effect of the Flipped Classroom model in improving the mufradat mastery of fifth-grade students at MIN 1 Karanganyar. The research method employed a quantitative approach with a pre-experimental design (one-group pretest-posttest design). The research subjects consisted of 27 fifth-grade students selected through purposive sampling. Data were collected using multiple-choice tests before and after the intervention, then analyzed using normality, homogeneity, and paired sample t-tests with the assistance of SPSS version 26. The results of the study showed a significant increase in mufradat mastery after the implementation of the Flipped Classroom, as indicated by the statistically significant difference between the pretest (M = 29.63) and posttest (M = 77.04) scores (p = 0.000). This study contributes theoretically by reinforcing previous findings on the effectiveness of the Flipped Classroom in language learning, but with a specific focus on mufradat mastery at the elementary madrasah level, which has been relatively understudied. In practical terms, this study provides a reference for teachers, madrasahs, and parents to optimize mufradat learning through the synergy of pre-class stages, class discussions, and integrated evaluation-reflection with technological support. Thus, this study confirms that the Flipped Classroom can be a relevant, innovative, and applicable alternative learning model to improve the quality of students’ mufradat mastery from the elementary level.